Evaluation of the natural perinatal transmission of bovine leukaemia virus. (7th March 2015) - Mekata, Hirohisa; Sekiguchi, Satoshi; Konnai, Satoru; Kirino, Yumi; Honkawa, Kazuyuki; Nonaka, Nariaki; Horii, Yoichiro; Norimine, Junzo
Abstract : The perinatal transmission of bovine leukaemia virus (BLV) plays a critical role in the spread and persistence of BLV infection in cattle herds. The purpose of this study was to examine the frequency of perinatal infections in an area in Japan and investigate some risk factors associated with infection. Altogether, 129 calves born to BLV‐infected cows in a herd in Japan were tested for infection immediately after birth and again at one month of age using nested PCR. Twenty‐four calves (18.6 per cent) were infected with BLV, of which 14 (10.8 per cent) and 10 (7.7 per cent) calves were infected via the transplacental and the birth canal routes, respectively. Maternal viral loads, breed, the presence or absence of assistance during parturition and the number of births per dam were evaluated to investigate risk factors associated with infection. Maternal viral load was significantly correlated with the frequency of perinatal infection, and more than 40 per cent of newborn calves born to dams with high viral loads were infected with BLV. The results of this study could contribute towards developing effective eradication programmes by providing necessary data for replacement of breeding cow in the field.